Re-Imagining Sexual Harassment Perspectives from the Nordic Region - Lundqvist, Maja; Simonsson, Angelica; Widegren, Kajsa (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book looks at what a Nordic perspective can teach us about sexual harassment. Bringing researchers, writers and policy makers into dialogue in an ambitious volume, the book moves beyond the juridical definitions of justice, coloniality, exploitation and work and offers knowledge that is immediately implementable into policy making.